An Empirical Analysis on the Determinants of Chinese Commercial Banks's Profitability during the period 2011-2016 - LIU, YANG (2018)
This study examines the determinants of bank profitability based on a sample of 45 listed commercial banks which including 5 large state-owned commercial banks, 9 joint-equity commercial banks, 22 urban commercial banks and 9 rural commercial banks during the period from 2011 to 2016 in China. The method for this study is the two-step System Generalized Method of Moments (SGMM) which is applied to estimate the dynamic panel data regression model. Moreover, the variables are divided into bank-specific variables and macroeconomic variables. To be specific, the bank-specific variables are from various aspects, i.e., bank size, liquidity, asset quality, capital adequacy and insolvency risk. The macroeconomic variables are the real interest rate, unemployment rate and inflation. The final results show different impacts from different determinants.